NEW DIRECTIONS FOR THE COSTS OF EVALUATION - Tascovici, Daliana; Dragomir, Robert; Isbasoiu, Eliza; Zarnescu, Odi Mihaela (Annals of Spiru Haret University. Economic Series, 2013)
The present paper presents at first ideas about how evaluation can play a key role in the educational reform. Thus, a great variety of data sources, new social power relations and changed ways of thinking about evaluation are required. The new directions for the teachers’ evaluation utter that a good evaluation has to assure the audience and also offer a main source of reward and recognition for teachers. It also pretends both the teachers’ participation and control. An important issue the pedagogues consider at present is the cost of evaluation: there are different evaluation costs: evaluation costs in terms of money, in terms of time, in terms of materials and morale costs. In its second part, the paper presents several types of data source for teacher evaluation: the pupil reports, teacher tests, documentation of professional activity, systematic observation, dossier assembly and the specific cost for each and every presented approach in the American society and for comparison the costs – as they are seen – in the Romanian system of learning.